2010
DOI: 10.1091/mbc.e10-03-0246
|View full text |Cite
|
Sign up to set email alerts
|

Centriolar Association of ALMS1 and Likely Centrosomal Functions of the ALMS Motif–containing Proteins C10orf90 and KIAA1731

Abstract: This study reveals the subcentrosomal distribution of ALMS1, a human protein implicated in primary cilium formation and maintenance, and provides new insight into its centrosome-related functions. The first functional data on two human proteins sharing C-terminal sequence similarity with ALMS1 are also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(122 citation statements)
references
References 67 publications
7
115
0
Order By: Relevance
“…Consistent with the previous report (Knorz et al, 2010), knockdown of CEP295 by siRNA quickly resulted in centrosome number reduction (Figure 2A). The same defect was also seen by CRISPR/Cas9-mediated gene targeting (Figure 2B) (Mali et al, 2013).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with the previous report (Knorz et al, 2010), knockdown of CEP295 by siRNA quickly resulted in centrosome number reduction (Figure 2A). The same defect was also seen by CRISPR/Cas9-mediated gene targeting (Figure 2B) (Mali et al, 2013).…”
Section: Resultssupporting
confidence: 93%
“…The study of one protein KIAA1731, hereafter named CEP295, was presented. KIAA1731/CEP295 has been previously characterized as an essential factor for centriole assembly or stability (Knorz et al, 2010), but its exact role in centriole biogenesis and maintenance remains unclear. Our immunofluorescence studies showed that CEP295 associates with both of the (converted) centrioles during G1 (Figure 1A), but becomes more enriched at the newly formed daughter (or unconverted) centrioles during S, G2 and early M phases (Figure 1A & C), a pattern distinct from other known daughter centriole proteins.…”
Section: Resultsmentioning
confidence: 99%
“…28,55 A change in centriole composition may therefore be how loss of the centrosome cohesion proteins affects ciliogenesis. In conclusion, our data suggest that the proteins that tether G 2 centrosomes also control disengaged centriole behavior and ciliogenesis after irradiation.…”
Section: Supplemental Materialsmentioning
confidence: 99%
“…Although located at the C-terminus of the transcript, the frameshift occurs directly within the ALMS motif (residues 4035-4167) which is part of the C-terminal portion of ALMS1 that contributes to centrosome targeting. Examination of ALMS1 localization to the centrosomes by Knorz and colleagues showed that constructs lacking the 3' end (3176-4167) of ALMS1 show diffuse or less compact chromosomal staining and constructs missing from residues 5 onwards show no detectable centrosomal staining [9]. Therefore, based on the work of Knorz and colleagues, it is likely that both mutant proteins identified in the affected siblings will show reduced or absent localization to the centrosomes.…”
Section: Discussionmentioning
confidence: 99%